Hot carrier solar cell with semi infinite energy filtering. (January 2015) - Konovalov, I.; Emelianov, V.; Linke, R.
Graphical abstract: Highlights: Simple design of hot carrier solar cell with double heterostructure. Electrochemical fabrication of InP/PbSe heterostructure. Valence band offset 0.3 eV and conduction band offset 0.8 eV for InP/PbSe interface. Double beam experiment for probing carrier–carrier energy transfer. Optoelectrical observation of hot carrier extraction at room temperature. Abstract: Energy filtering of hot carriers in a solar cell may be attained by using band offsets at heterointerfaces. This rough energy filtering does not require special sophisticated energy filtering contacts, and may be implemented in the form of a double heterojunction. PbSe thin film as absorber layer was electrodeposited on InP single crystal. Experimental evidence of hot carrier filtering at InP/PbSe heterointerface at room temperature was obtained by double beam optoelectrical measurements. The measurements can be interpreted by thermionic emission over the band offset barriers. The valence band offset of 0.3 eV at the InP/PbSe heterointerface was measured by X-ray Photoelectron Spectroscopy. The filtering process may become useful for new generation of hot carrier solar cells.